A anterioridade das leis tributárias - Melo, Ana Carolina de Paula Leal de (2008)
The subject chosen for scientific research was THE LEGAL SYSTEM FOR ANTERIORITY OF TAX LAWS (the publication of tax laws before the tax year to which they apply). This came to our attention when the Constitutional Amendment n° 42/2003 was announced, which alters the constitutional text, introducing paragraph c in clause III of article 150 of the Federal Constitution, that institutes special anteriority. We wish to give our contribution, though small, to Legal Science, seeking to scrutinise the inquiry objective: The Principle of the Anteriority. We know that no description comes close to reality, which is inexhaustible for cognoscitive ends, as it is inevitable that there will be some distancing between the object and the judgement constructed by the person knowing about the topic. Thus we will be please as we will have reached our objective if the work contributes scientifically to the study of Law, and to future inquiries into same subject. In this study our aim is to define the reach of the principle of Anteriority, keeping in mind that the subject is extremely important for Law, especially Tax Law, since it is a fundamental principle of the legal system, and has direct influence on taxation, as well as by the fact of being a principle that guarantees the compliance of other constitutional principles, such as the security of the judicial system, and legality. While developing this study, we had chance to verify that the principle of Anteriority appears in the constitutional text in more than one form. (The Ninety Day Anteriority Law), which we study in great detail in this work. Later, when we study the subject in greater depth, we come across various circumstances that could influence decisively the application or not of principle of anteriority. We also analyse related aspects of the subject, such as its inception and reasons that led the formation of the anteriority law, and the ninety day anteriority law. Later there were reasons to istitute the Special Anteriority Law. The work also analyse the terms To institute and to increase , looking to identify the consequences and outcomes that these terms have in the legal sistem. We also came across some controversial questions, such as how to measure the time period for compliance of the principle of anteriority, as well as that its legality, the time period or its effectiveness that influences the counting of the time period of the cited principle. And finally, we analyse the relationship between the principle of anteriority and the provisional laws (valid for 90 days). Finally we were able to debate how to resolve in a scientific way questions that, we hope, are useful in the development of the subject following the best teaching methods, and in Brazilian courts